Wedding Culture of Urang Serawai Sintang - Fajriati, Debi (The Pontianak State Institute of Islamic Studies, 2018)
This article describes the urang Serawai bride culture in Sintang District, West Kalimantan. The description was carried out because the author was interested in seeing the form of bride culture in Muslim communities living in remote areas which is far from the center of Islam. The data used in this paper is based on interviews with cultural actors and observations of wedding activities in 2015, coupled with own experience as part of the Serawai community. In the Urang Serawai bride culture there is a series of activities. In the activity, it shows the elements of Islam, such as reciting the Koran, prayer, barzanji, hadrah, etc.; and there are local elements, for example, seen in parade, nopen, janur, etc. Through the bride culture, it appears that Islam and local culture are side by side, filling in the space and function of each.